The Role of Digital Mindset and Digital Adaptation Skills in Mediating the Digital Learning Environment on the Digital Competence of Generation Z Students in Sumenep Regency: Peran Pola Pikir Digital dan Keterampilan Adaptasi Digital Dalam Memediasi Lingkungan Belajar Digital Terhadap Kompetensi Digital Mahasiswa Generasi Z di Kabupaten Sumenep - Aryo Wibisono; Mohammad Firlie Pranata; Nur Inna Alfiyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Generation Z is closely related to the digital world, therefore teaching methods in lectures should be more inclined towards the use of digital devices, such as the implementation of online lectures, the use of applications in solving problems so that they can form a more developed digital mindset of students. Because in the future work will be inclined to the use of technology, so that later students who have graduated can easily adapt to the world of work. The purpose of this study is to see the Role of Digital Mindset and Digital Adaptation Skills in Mediating the Digital Learning Environment on the Digital Competence of Generation Z Students in Sumenep Regency. The sample in this study is students who are still actively studying at universities in Sumenep Regency, with a total of 96 respondents. The results showed that LBD had a positive and significant effect on KAD and PPD, and both had a significant effect on KD. However, the direct influence of LBD on KD was not significant, indicating that the relationship occurred through the mediation role of KAD and PPD. An R-square value of 0.609 indicates that the model has a moderate ability to explain students' digital competence. These findings confirm that strengthening the digital learning environment will be more effective if it is balanced with increasing students' adaptability to technology and forming a positive perception of digital learning. The practical implications of this study emphasize the importance of collaboration between educational institutions, lecturers, and students in creating a digital learning ecosystem that supports the continuous improvement of digital competencies